An elevated percentage of CD4⁺CD25⁺CD127low regulatory T cells in peripheral blood indicates a poorer prognosis in hepatocellular carcinoma after curative hepatectomy - Haoran Sun; Zepeng Cao; Baochen Zhao; Dachen Zhou; Zhongbiao Chen; Bin Zhang (BMC Gastroenterology)
Abstract Background Previous studies suggest the percentage of CD4⁺CD25⁺CD127low regulatory T cells (Tregs) in peripheral blood of patients with hepatocellular carcinoma (HCC) was significantly higher than that in healthy, which may be a significant predictor of HCC clinical outcome, and we examined the utility of Tregs in predicting prognosis in HCC after curative hepatectomy. Methods 77 diagnosed HCC patients from August 2018 to March 2023 were selected as research objects, we retrospectively analyzed whether the preoperative percentage of CD4⁺CD25⁺CD127low Tregs in peripheral blood predicts prognosis after curative hepatectomy in HCC patients. The percentage of CD4⁺CD25⁺CD127low Tregs was detected by flow cytometry. Results The percentage of CD4⁺CD25⁺CD127low Tregs was significantly elevated in patients who developed recurrence and death (p < 0.050). X-tile software was used to calculate optimal cut-off value of Treg percentage (5.85%), and patients were divided into two groups with high and low Treg percentage. Patients with higher preoperative Treg percentage had a significantly poorer prognosis (p < 0.050). Cox regression demonstrated the percentage of CD4⁺CD25⁺CD127low Tregs was an independent indicator for poor prognosis after hepatectomy. The Recurrence-free survival (RFS) (the log-rank test, p < 0.001) and Overall survival (OS) (the log-rank test, p = 0.008) in patients with higher Treg percentage were significantly lower than that in patients with lower Treg percentage. The results were confirmed by the subgroup analysis. Conclusion The percentage of CD4⁺CD25⁺ CD127low Tregs in peripheral blood is associated with poor prognosis in HCC patients. It can be suggested as a potential prognostic indicator for HCC patients after hepatectomy and complement existing risk stratification tools. Measuring the percentage of CD4⁺CD25⁺ CD127low Tregs may contribute to the formulation of treatment strategies and the improvement of the prognosis for HCC patients.